EVALUATION OF NUTRITION AND GLYCEMIC INDEX OF SWEET POTATOES AND ITS APPROPRIATE PROCESSING TO HYPOGLYCEMIC FOODS - Astawana, Made; Widowati, Sri (Indonesian Journal of Agricultural Science, 2011)
Indonesia placed the fourth biggest diabetics in the world after India, China, and the USA with prevalence amounting to 8.6% of the population. Diabetes is an abnormal carbohydrate metabolism. Therefore, nutrition plays a key role in the management of the disease. This study aimed to find hypoglycemic sweet potatoes and appropriate processing to create low glycemic foods. Eight Indonesian sweet potato varieties/clones were used in this experiment, i.e. Kidal, Sukuh, Sari, Ungu, Jago, BB00105.10, B0464, and BB00106.18. Samples were firstly analyzed for their physicochemical and nutritional properties, which then followed by evaluation of their hypoglycemic responses. The selected variety was processed into three different basic processing methods, i.e. boiling, baking, and frying, and then their glycemic indexes (GI) were evaluated. Result showed that among eight sweet potato varieties/clones studied, BB00105.10 clone indicated the best hypoglycemic response. The highest hypoglycemic activity was supported with the highest resistant starch content (3.8%), protein content (5.47%), and low starch digestibility (51.4%). The sweet potato tubers contained medium to high amylose (24.94%). Processing methods influenced the GI value of foods. Fried sweet potatoes had the lowest GI (47), followed by the boiled one (GI = 62) and the baked one (GI = 80).